Predictors for participation in mass-treatment and female genital schistosomiasis re-investigation, and the effect of praziquantel treatment in South African adolescents. - Takalani Girly Nemungadi; Elisabeth Kleppa; Hashini Nilushika Galappaththi-Arachchige; Pavitra Pillay; Svein Gunnar Gundersen; Birgitte Jyding Vennervald; Patricia Doris Ndhlovu; Myra Taylor; Saloshni Naidoo; Eyrun Floerecke Kjetland (PLoS Neglected Tropical Diseases)
Objective Female Genital Schistosomiasis (FGS) causes intravaginal lesions and symptoms that could be mistaken for sexually transmitted diseases or cancer. In adults, FGS lesions [grainy sandy patches (GSP), homogenous yellow patches (HYP), abnormal blood vessels and rubbery papules] are refractory to treatment. The effect of treatment has never been explored in young women; it is unclear if gynaecological investigation will be possible in this young age group (16-23 years). We explored the predictors for accepting anti-schistosomal treatment and/or gynaecological reinvestigation in young women, and the effects of anti-schistosomal mass-treatment (praziquantel) on the clinical manifestations of FGS at an adolescent age. Method The study was conducted between 2011 and 2013 in randomly selected, rural, high schools in Ilembe, uThungulu and Ugu Districts, KwaZulu-Natal Province, East Coast of South Africa. At baseline, gynaecological investigations were conducted in female learners in grades 8 to 12, aged 16-23 years (n = 2293). Mass-treatment was offered in the low-transmission season between May and August (a few in September, n = 48), in accordance with WHO recommendations. Reinvestigation was offered after a median of 9 months (range 5-14 months). Univariate, multivariable and logistic regression analysis were used to measure the association between variables. Results Prevalence: Of the 2293 learners who came for baseline gynaecological investigations, 1045 (46%) had FGS lesions and/or schistosomiasis, 209/1045 (20%) had GSP; 208/1045 (20%) HYP; 772/1045 (74%) had abnormal blood vessels; and 404/1045 (39%) were urine positive. Overall participation rate for mass treatment and gynaecological investigation: Only 26% (587/2293) learners participated in the mass treatment and 17% (401/2293) participated in the follow up gynaecological reinvestigations. Loss to follow-up among those with FGS: More than 70% of learners with FGS lesions at baseline were lost to follow-up for gynaecological investigations: 156/209 (75%) GSP; 154/208 (74%) HYP; 539/722 (75%) abnormal blood vessels; 238/404 (59%) urine positive. The grade 12 pupil had left school and did not participate in the reinvestigations (n = 375; 16%). Follow-up findings: Amongst those with lesions who came for both treatment and reinvestigation, 12/19 still had GSP, 8/28 had HYP, and 54/90 had abnormal blood vessels. Only 3/55 remained positive for S. haematobium ova. Factors influencing treatment and follow-up gynaecological investigation: HIV, current water contact, water contact as a toddler and urinary schistosomiasis influenced participation in mass treatment. Grainy sandy patches, abnormal blood vessels, HYP, previous pregnancy, current water contact, water contact as a toddler and father present in the family were strongly associated with coming back for follow-up gynaecological investigation. Challenges in sample size for follow-up analysis of the effect of treatment: The low mass treatment uptake and loss to follow up among those who had baseline FGS reduced the chances of a larger sample size at follow up investigation. However, multivariable analysis showed that treatment had effect on the abnormal blood vessels (adjusted odds ratio = 2.1, 95% CI 1.1-3.9 and p = 0.018). Conclusion Compliance to treatment and gynaecological reinvestigation was very low. There is need to embark on large scale awareness and advocacy in schools and communities before implementing mass-treatment and investigation studies. Despite challenges in sample size and significant loss to follow-up, limiting the ability to fully understand the treatment's effect, multivariable analysis demonstrated a significant treatment effect on abnormal blood vessels.